144 Effects of Increasing Dietary Standardized Ileal Digestible Lysine Levels on Growth Performance of 15- to 23-Kg Maternal Barrows. (12th April 2022) - Vier, Carine M; Lu, Ning; Dritz, Steve; Estrada, Jorge; Peterson, Beau; Hanson, Andrea; Cast, Wayne R; Wells, Danielle; Orlando, Uislei A
Abstract: Our objective was to determine the effects of increasing dietary standardized ileal digestible (SID) lysine (Lys) on growth performance of late nursery pigs. A total of 1, 125 barrows (L02 ′ L03, initially 15.4 kg ± 0.003) were used in a 14-d study. Pens of pigs were weighed, blocked by location in the barn, and randomly allotted to 1 of 6 treatments that contained 1.05, 1.16, 1.23, 1.29, 1.39, and 1.52% of dietary SID Lys. Diets were corn-soybean meal-based and contained 3, 300 Kcal of ME/kg, with treatments achieved by increasing the inclusion of synthetic lysine. There were 9 pens per treatment and 25 barrows per pen. Data were analyzed using generalized linear and nonlinear mixed models with pen as the experimental unit. Competing models included linear, quadratic polynomial (QP), broken-line linear (BLL), and broken-line quadratic (BLQ). Increasing SID Lys concentration improved average daily gain (ADG; linear, P < 0.05) and gain to feed ratio (G:F; quadratic, P < 0.05). Although no model provided better fit to the ADG data compared with the linear model, the greatest improvement in growth rate was observed as SID Lys increased from 1.05 to 1.41%. The best-fitting models for G:F were QP and BLL. The QP and BLL models estimated the plateau or breakpoint at dietary SID Lys of 1.45% (95% CI: 1.21 to >1.52%) and 1.41% (95% CI: 1.40 to 1.42%), respectively. There was no evidence that increasing dietary SID Lys levels impacted average daily feed intake or the removal and mortality rate ( P > 0.10). Increasing SID Lys concentration increased (linear; P < 0.05) the grams of SID Lys intake per kg of gain. In the current trial, the estimated optimum SID Lys concentration for 15- to 23-kg maternal barrows ranged from 1.41 to 1.46%, depending on the statistical model.